Effect of interferon on the growth of Chlamydia trachomatis in mouse fibroblasts (L cells). - Rothermel, C D (1983)
The effect of murine interferon on the growth of the lymphogranuloma venereum biotype of Chlamydia trachomatis (strain 440L) in murine fibroblasts (L cells) was examined. Treatment of infected cell cultures with interferon caused a reduction in the number of inclusion-bearing cells as seen by light and electron microscopy and a decrease in yields of chlamydiae as determined by infectivity assays. Interferon also inhibited cycloheximide-resistant (chlamydia-specific) protein synthesis in infected cells. The interferon effect was dose dependent, with 80 to 90% inhibition occurring at concentrations of greater than 200 IU/ml. The inhibitory effect was neutralized by anti-murine interferon globulin. Interferon did not inactivate extracellular chlamydiae, and both host cell RNA and protein synthesis were required for the development of the interferon-induced antichlamydial state. Inhibition of chlamydial growth by interferon was demonstrable in cells treated 18 h before infection or up to 4 h after infection. Cells infected after interferon was removed exhibited an antichlamydial activity decline which was complete by 30 h after interferon removal. We show that interferon treatment did not affect either entry of chlamydiae into host cells or chlamydial conversion to reticulate bodies but rather caused a reduction in the rate of reticulate body replication.